2009
DOI: 10.1183/09031936.00086608
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cardiovascular disease in OSAHS: the oxidative stress link

Abstract: Obstructive sleep apnoea/hypopnoea syndrome (OSAHS) is a highly prevalent breathing disorder in sleep that is an independent risk factor for cardiovascular morbidity and mortality. A large body of evidence, including clinical studies and cell culture and animal models utilising intermittent hypoxia, delineates the central role of oxidative stress in OSAHS as well as in conditions and comorbidities that aggregate with it. Intermittent hypoxia, the hallmark of OSAHS, is implicated in promoting the formation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
228
2
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 234 publications
6
228
2
15
Order By: Relevance
“…9,10 Intermittent hypoxia is associated with increased production of reactive oxygen species, and therefore, increases oxidative stress. 70,71 Prolonged oxidative stress disturbs cellular function, promotes endothelial dysfunction and increases inflammation, which can further increase the metabolic and cardiovascular complications of OSA such as atherosclerosis. 70 Oxidative stress also reduces the activity of nitric oxide synthase and thus leads to decreased production of nitric oxide, increasing arterial stiffness.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Intermittent hypoxia is associated with increased production of reactive oxygen species, and therefore, increases oxidative stress. 70,71 Prolonged oxidative stress disturbs cellular function, promotes endothelial dysfunction and increases inflammation, which can further increase the metabolic and cardiovascular complications of OSA such as atherosclerosis. 70 Oxidative stress also reduces the activity of nitric oxide synthase and thus leads to decreased production of nitric oxide, increasing arterial stiffness.…”
Section: Mechanismsmentioning
confidence: 99%
“…70,71 Prolonged oxidative stress disturbs cellular function, promotes endothelial dysfunction and increases inflammation, which can further increase the metabolic and cardiovascular complications of OSA such as atherosclerosis. 70 Oxidative stress also reduces the activity of nitric oxide synthase and thus leads to decreased production of nitric oxide, increasing arterial stiffness. 72 Various studies have also found that C-reactive protein, tumor necrosis factor-a, interleukin-6 (IL-6), IL-8 and cell adhesion molecules such as intercellular adhesion molecule-1 are increased in the circulation in OSA patients independent of obesity.…”
Section: Mechanismsmentioning
confidence: 99%
“…The unique oxygen desaturation pattern seen in OSA produces tissue hypoxemia and re‐oxygenation similar to ischemia–reperfusion injury. Low oxygen saturation has been associated with impaired endothelial function,7 sympathetic activation,8 inflammation,9 hypercoagulation,10 oxidative stress,11 and metabolic disorders,12 all of which may increase the risk of MI. Clinically, nocturnal oxygen desaturation is independently associated with prevalence of cardiovascular diseases,13 correlates well with severity of coronary atherosclerosis using invasive coronary angiography,14 and may be an independent predictor of mortality 15.…”
Section: Introductionmentioning
confidence: 99%
“…OSA and associated IH have been demonstrated to independently contribute to the development of low-grade systemic inflammation (6), with increased expression of NF-κB dependent cytokines in both clinical subjects (127) and in vitro models of disease (128). Similarly, a significant evidence base supports the notion that OSA is an oxidative stress disorder, with reactive oxygen and nitrogen species likely formed at least partially due to IH-mediated mitochondrial dysfunction (93). Nocturnal CPAP therapy may lead to an abrogation of both systemic inflammation and oxidative stress, suggesting that appropriate treatment may obviate any pro-carcinogenic effect of OSA.…”
Section: Systemic Inflammation and Oxidative Stressmentioning
confidence: 72%